Data Visualization of the Maturity Level From the Perspective of Business-IT Alignment at PT. XYZ - Juwita, Oktalia; Arifin, Fajrin Nurman; Ailsya , Rachma; Nugrahani, Tri Agustina (Information Systems - Universitas Pesantren Tinggi Darul Ulum, 2024)
This article presents descriptive information about the results of the performance analysis and the maturity of the business-IT alignment process at PT.XYZ through the implementation of data-based visualization techniques within the SAMM perspective. This research is divided into four stages: preliminary research, data collection, data analysis, and organizational development analysis. Based on the results of the analysis using SAMM from the perspective of top-level management of an organization, PT. XYZ has achieved maturity in the attribute of good cooperation. This indicates that the company and organization understand the need for business-IT alignment for their development. However, the attainment level of maturity in the skills and communication attributes is less than optimal. This impacts the communication process and the distribution of information in the company’s development through IT implementation. This research only provides data visualization of the maturity achievements of PT. XYZ’s business alignment and information technology are based on the SAMM method. The process of analyzing the company's strategic alignment data and providing recommendations for implementing Information Technology to optimize the company's business was not included in this research.